Case Report: Atypical post-COVID Cogan's syndrome [version 2; peer review: 2 approved] - Sayhi Sameh; Chaima Zitouni; Mayssa Bouzidi; Wafa Sleimi; Sameh Mezri (F1000Research)
Background Cogan’s syndrome is a rare autoimmune disorder characterized by ocular inflammation, vestibulocochlear dysfunction, and systemic vasculitis. Case Presentation We report a 28-year-old female who experienced decreased visual acuity and ocular redness one month after a COVID-19 infection, with ophthalmological signs linked to keratitis, uveitis and retinal vasculitis. Two weeks later, she developed vertigo, tinnitus, and sudden hearing loss, leading to a diagnosis of Cogan’s disease. The patient received corticosteroid therapy, resulting in regression of ophthalmological signs, but progressed to complete deafness. One month later, she presented with lymphocytic meningitis and high intracranial pressure, which improved under treatment. The patient later received cochlear implants. Objective This case report aims to highlight an atypical presentation of Cogan’s syndrome with neurological involvement following a COVID-19 infection. This case contributes to the limited literature on such presentations. Conclusion Our case is one of only two reported instances of Cogan’s syndrome presenting with neurological signs post-COVID-19 infection, underscoring the rarity and complexity of this condition.